Association of eumycetoma and schistosomiasis. - Jaap J van Hellemond; Alieke G Vonk; Corné de Vogel; Rob Koelewijn; Norbert Vaessen; Ahmed H Fahal; Alex van Belkum; Wendy W J van de Sande (Public Library of Science (PLoS), 2013)
Eumycetoma is a morbid chronic granulomatous subcutaneous fungal disease. Despite high environmental exposure to this fungus in certain regions of the world, only few develop eumycetoma for yet unknown reasons. Animal studies suggest that co-infections skewing the immune system to a Th2-type response enhance eumycetoma susceptibility. Since chronic schistosomiasis results in a strong Th2-type response and since endemic areas for eumycetoma and schistosomiasis do regionally overlap, we performed a serological case-control study to identify an association between eumycetoma and schistosomiasis. Compared to endemic controls, eumycetoma patients were significantly more often sero-positive for schistosomiasis (p = 0.03; odds ratio 3.2, 95% CI 1.18-8.46), but not for toxoplasmosis, an infection inducing a Th1-type response (p = 0.6; odds ratio 1.5, 95% CI 0.58-3.83). Here, we show that schistosomiasis is correlated to susceptibility for a fungal disease for the first time.